Development of an Epstein–Barr virus‐associated lymphoproliferative disorder in a patient treated with azacitidine for chronic myelomonocytic leukaemia. Issue 1 (29th April 2013) - Menter, T; Schlageter, M; Bastian, L; Haberthür, R; Rätz Bravo, AE; Tzankov, A
Abstract Some chemotherapeutic agents can cause iatrogenic lymphoproliferative disorders. In analogy to what has been observed with other nucleoside analogues such as cladribine and fludarabine, we document the first case of an Epstein–Barr virus‐positive, iatrogenic immunodeficiency‐associated, lymphoproliferative disease, formally resembling polymorphic post‐transplant lymphoproliferative disease in a patient treated with azacitidine (Vidaza) for chronic myelomonocytic leukaemia (CMML). A 78‐year‐old female patient was diagnosed with CMML in January 2012, and treatment with azacitidine was initiated, which lasted for five cycles from February until June 2012. The patient was hospitalized in June 2012 under the suspicion of pneumonia. Transformation of the CMML was suspected at that time too. During hospitalization, a generalized enlargement of the lymph nodes and the spleen was noticed. The patient rapidly deteriorated and finally died of respiratory insufficiency. At autopsy, an Epstein–Barr virus‐associated lymphoproliferative disorder, resembling polymorphic post‐transplant lymphoproliferative disease with involvement of the lymph nodes, the spleen and the lung and causing necrotizing pneumonia, was diagnosed. Diagnostic criteria for diffuse large B‐cell lymphoma or infectious mononucleosis‐like lymphoproliferative disease were not met. This is the first documented case of an azacitidine‐associated lymphoproliferative disease, raising awareness for possible not yet known side effects of this drug, which should be kept in mind by oncologists and pathologists. Copyright © 2013 John Wiley & Sons, Ltd.